The Basic Science of the Patella: Structure, Composition, and Function - Fox, Alice J. S.; Wanivenhaus, Florian; Rodeo, Scott A. (The Journal of Knee Surgery, 2012)
The patella is the largest sesamoid bone in the body. The patellofemoral joint provides an integral articulating component of the extensor mechanism of the knee joint. A detailed description of patella anatomy, embryology and development, neurovascular anatomy, biomechanical function, and imaging modalities is provided in this article. Common patellar pathologies such as patellar instability, trochlear dysplasia, patella alta and baja, and patellofemoral joint arthritis as well as patellofemoral arthroplasty as a treatment option are also discussed. An understanding of the normal anatomy and biomechanics of the patella is a necessary prerequisite for understanding the pathogenesis of disorders involving the knee.
Keywords: patella; basic science; anatomy; patellofemoral joint; biomechanics